2022
DOI: 10.2147/cmar.s373165
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Liquid Biopsy Techniques in High-Risk Population for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors of the digestive system and has a 5-year overall survival rate of 14.1%. Many HCC patients are diagnosed at an advanced stage, and thus early screening is essential for reducing the mortality of HCC. In addition to commonly used detection indicators such as serum alpha-fetoprotein (AFP), lens culinaris agglutinin-reactive fraction of alpha-fetoprotein (AFP-L3) and abnormal prothrombin (protein induced by vitamin K absence II, PIVKA-II), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…A number of recent studies have demonstrated the potential of liquid biopsy for cancer screening, refinement of diagnosis, and early of cancer recurrences [43,61]. By detecting circulating tumor cells, nucleic acids, and exosomes, the method can be used for early cancer detection, diagnosis, and prognosis in various types of cancer [35,63,71,149]. Additionally, liquid biopsy can provide insights into cancer progression and treatment response by assessing cancer cachexia, muscle-derived microRNAs, and energy metabolism [16].…”
Section: Early Detection and Diagnosismentioning
confidence: 99%
“…A number of recent studies have demonstrated the potential of liquid biopsy for cancer screening, refinement of diagnosis, and early of cancer recurrences [43,61]. By detecting circulating tumor cells, nucleic acids, and exosomes, the method can be used for early cancer detection, diagnosis, and prognosis in various types of cancer [35,63,71,149]. Additionally, liquid biopsy can provide insights into cancer progression and treatment response by assessing cancer cachexia, muscle-derived microRNAs, and energy metabolism [16].…”
Section: Early Detection and Diagnosismentioning
confidence: 99%
“…Liquid biopsy is potentially used for screening high-risk populations for early cancer detection. High-risk populations are more susceptible to cancer development due to previous cancer treatments, family history, genetic mutations, and exposure to carcinogens, which involves analyzing the circulatory metabolites of malignant neoplasm or other body fluids [ 29 ]. RNA-Seq analysis of platelet-derived RNA can detect both early- and late-stage NSCLC with an accuracy of around 80%, which involves sequencing the RNA molecules of platelets and analyzing gene expression patterns [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Somatic mutations, such as BRAF and RAS detection in ctDNA, improve treatment response and survival outcomes. ctDNA levels predict tumor response to immunotherapy and evaluate markers such as microsatellite instability (MSI) and tumor mutational burden (TMB) [ 29 ]. The presence of specific exosomal miRNAs, long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) are biomarkers for diagnosing cancer, predicting prognosis, and assessing treatment response.…”
Section: Reviewmentioning
confidence: 99%